2014
DOI: 10.1097/igc.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perioperative Outcomes and Complication Rates Between Conventional Versus Robotic-Assisted Laparoscopy in the Evaluation and Management of Early, Advanced, and Recurrent Stage Ovarian, Fallopian Tube, and Primary Peritoneal Cancer

Abstract: In our experience, perioperative outcomes are comparable between CL and RALS in both early and advanced/recurrent disease and not inferior to laparotomy, making CL and RALS an acceptable approach in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…Our perioperative outcomes, including the median blood loss, the median hospital stay, and the intraoperative complications, are in accordance with that reported in other studies and globally better than results from studies on laparotomic series. 23 In conclusion, laparoscopic cytoreduction in patients with advanced ovarian cancer after NACT, when performed by skilled surgeons and in a selected cohort of patients, seems feasible and may decrease the impact of aggressive surgery on high-morbidity patients, such as on women after undergoing chemotherapy. Advances in laparoscopic instrumentation and technique have made a laparoscopic approach to surgical cytoreduction possible in selected patients.…”
Section: Discussionmentioning
confidence: 89%
“…Our perioperative outcomes, including the median blood loss, the median hospital stay, and the intraoperative complications, are in accordance with that reported in other studies and globally better than results from studies on laparotomic series. 23 In conclusion, laparoscopic cytoreduction in patients with advanced ovarian cancer after NACT, when performed by skilled surgeons and in a selected cohort of patients, seems feasible and may decrease the impact of aggressive surgery on high-morbidity patients, such as on women after undergoing chemotherapy. Advances in laparoscopic instrumentation and technique have made a laparoscopic approach to surgical cytoreduction possible in selected patients.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, other authors have reported similar lymph node yields and survival with the robot-assisted approach compared with laparotomy (5,42). In 2014 Nezhat et al compared 47 cytoreductive procedures in stages II-IV and recurrent cancer and found similar maximal cytoreduction and complication rates in robot-assisted, laparoscopy, and laparotomy (43).…”
Section: Ovarian Cancermentioning
confidence: 96%
“…Removal of the infrarenal aortic nodes, in particular the left group, can be challenging due to the presence of large vessels, frequent anatomical vessel anomalies of this area, close proximity of the camera port and narrow operative field . Data describing robot‐assisted staging of early‐stage ovarian cancers is limited (Table ) . Nezhat et al .…”
Section: Resultsmentioning
confidence: 99%
“…In the early 1990s, laparoscopy was used for the staging of early ovarian cancer . Subsequently, its advantages over laparotomy became well established, including superior intraoperative visualization, smaller incisions, reduced blood loss, decreased postoperative complications such as wound infections and small bowel ileus, shorter hospitalization time and faster recovery . However, laparoscopy presented its own drawbacks; lack of depth perception, two‐dimensional (2D) optics, camera instability, reliance on skilled surgical assistance, counter‐intuitive hand motion, limited range of motion, non‐wristed instrumentation and protracted learning curves .…”
Section: Introductionmentioning
confidence: 99%